2020
DOI: 10.1186/s12939-020-1151-7
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide cross-sectional study of 15,611 lesbian, gay and bisexual people in China: disclosure of sexual orientation and experiences of negative treatment in health care

Abstract: Background: Lesbian, gay and bisexual (LGB) people often face individual-and system-level barriers in health care. However, LGB people's experiences of health care in non-European and non-American settings have been scarcely studied. In China, while it has been estimated that there are at least 70 million gender and sexual minorities, there has been no larger-scale study on LGB people's experiences of health care beyond a focus on gay men and HIV. This study is the first larger-scale quantitative study to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 38 publications
0
24
0
4
Order By: Relevance
“…Also, homosexuality was classified as a sexual disorder until it was eliminated from the Chinese Classification of Mental Disorders (CCMD) in 2001 (Wu, 2003). Nonetheless, diagnosis of "ego-dystonic sexual orientation" was still retained in CCMD, and unfortunately, nearly 6% of Chinese sexual minorities reported that they had been recommended by their mental health care providers to receive conversion therapy (Suen & Chan, 2020). Besides, some traditional customs, such as the filial piety, which values the continuation of family strain, may lead to some negative attitudes toward sexual minorities (Kwok & Wu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, homosexuality was classified as a sexual disorder until it was eliminated from the Chinese Classification of Mental Disorders (CCMD) in 2001 (Wu, 2003). Nonetheless, diagnosis of "ego-dystonic sexual orientation" was still retained in CCMD, and unfortunately, nearly 6% of Chinese sexual minorities reported that they had been recommended by their mental health care providers to receive conversion therapy (Suen & Chan, 2020). Besides, some traditional customs, such as the filial piety, which values the continuation of family strain, may lead to some negative attitudes toward sexual minorities (Kwok & Wu, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, in China, things look less rosy. It is estimated that China has over 70 million gender and sexual minorities 5 . They still face substantial challenges to safeguard their health and rights due to cultural and other factors existing for a long time 6 .…”
mentioning
confidence: 99%
“…The Chinese Government has contributed a lot in specific areas, such as the screening and prevention of HIV and syphilis among men who have sex with men 6 . However, many mental health workers in China still regard homosexuality as sexual perversion, and about 8.0% of the lesbian, gay, and bisexual people reported having experienced negative treatment in healthcare settings 5 . Sexual minorities are more vulnerable to underutilized health service, refusals of health care, and delayed or sub‐standard care 5 .…”
mentioning
confidence: 99%
See 2 more Smart Citations